Onasemnogene abeparvovec gene therapy for symptomatic infantile-onset spinal muscular atrophy type 1 (STR1VE-EU): an open-label, single-arm, multicentre, phase 3 trial. Issue 10 (October 2021) - Mercuri, Eugenio; Muntoni, Francesco; Baranello, Giovanni; Masson, Riccardo; Boespflug-Tanguy, Odile; Bruno, Claudio; Corti, Stefania; Daron, Aurore; Deconinck, Nicolas; Servais, Laurent; Straub, Volker; Ouyang, Haojun; et al.
Summary: Background: Spinal muscular atrophy is a rare, autosomal recessive, neuromuscular disease caused by biallelic loss of the survival motor neuron 1 ( SMN1 ) gene, resulting in motor neuron dysfunction. In this STR1VE-EU study, we aimed to evaluate the safety and efficacy of onasemnogene abeparvovec gene replacement therapy in infants with spinal muscular atrophy type 1, using broader eligibility criteria than those used in STR1VE-US. Methods: STR1VE-EU was a multicentre, single-arm, single-dose, open-label phase 3 trial done at nine sites (hospitals and universities) in Italy (n=4), the UK (n=2), Belgium (n=2), and France (n=1). We enrolled patients younger than 6 months (180 days) with spinal muscular atrophy type 1 and the common biallelic pathogenic SMN1 exon 7–8 deletion or point mutations, and one or two copies of SMN2 . Patients received a one-time intravenous infusion of onasemnogene abeparvovec (1·1 × 10 14 vector genomes [vg]/kg). The outpatient follow-up consisted of assessments once per week starting at day 7 post-infusion for 4 weeks and then once per month until the end of the study (at age 18 months or early termination). The primary outcome was independent sitting for at least 10 s, as defined by the WHO Multicentre Growth Reference Study, at any visit up to the 18 months of age study visit, measured in the intention-to-treat population. Efficacy was compared with the Pediatric Neuromuscular Clinical Research (PNCR) natural history cohort. This trial is registered with ClinicalTrials.gov, NCT03461289 (completed). Findings: From Aug 16, 2018, to Sept 11, 2020, 41 patients with spinal muscular atrophy were assessed for eligibility. The median age at onasemnogene abeparvovec dosing was 4·1 months (IQR 3·0–5·2). 32 (97%) of 33 patients completed the study and were included in the ITT population (one patient was excluded despite completing the study because of dosing at 181 days). 14 (44%, 97·5% CI 26–100) of 32 patients achieved the primary endpoint of functional independent sitting for at least 10 s at any visit up to the 18 months of age study visit ( vs 0 of 23 untreated patients in the PNCR cohort; p<0·0001). 31 (97%, 95% CI 91–100) of 32 patients in the ITT population survived free from permanent ventilatory support at 14 months compared with six (26%, 8–44) of 23 patients in the PNCR natural history cohort (p<0·0001). 32 (97%) of 33 patients had at least one adverse event and six (18%) had adverse events that were considered serious and related to onasemnogene abeparvovec. The most common adverse events were pyrexia (22 [67%] of 33), upper respiratory infection (11 [33%]), and increased alanine aminotransferase (nine [27%]). One death, unrelated to the study drug, occurred from hypoxic-ischaemic brain damage because of a respiratory tract infection during the study. Interpretation: STR1VE-EU showed efficacy of onasemnogene abeparvovec in infants with symptomatic spinal muscular atrophy type 1. No new safety signals were identified, but further studies are needed to show long-term safety. The benefit–risk profile of onasemnogene abeparvovec seems favourable for this patient population, including those with severe disease at baseline. Funding: Novartis Gene Therapies.